NEPAD and Castells : an interpretation of the NEPAD development framework in terms of the Network Society Theory - Heij, Anneliese (Anneliese Mari) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.